2018
DOI: 10.3892/or.2018.6807
|View full text |Cite
|
Sign up to set email alerts
|

E26 transformation (ETS)‑specific related transcription factor‑3 (ELF3) orchestrates a positive feedback loop that constitutively activates the MAPK/Erk pathway to drive thyroid cancer

Abstract: Thyroid cancer is the most commonly diagnosed malignancy of the endocrine system, the incidence of which has increased rapidly in the last 30 years. Genetic alterations in pathways, including the mitogen-activated protein kinase (MAPK)/extracellular signal-regulated kinase (Erk) and phosphatidylinositol-3-kinase (PI3K)/protein kinase B (Akt) pathways, are the driving force behind the development of differentiated thyroid cancer cases into aggressive and undifferentiated forms of thyroid cancer. E26 transformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…A light microscope (Olympus Corp.) was used to capture images to observe sample staining. To analyze the expression of PTPN1, the staining was categorized as previously described (11) and was confirmed by a pathologist at the First Affiliated Hospital of Xi'an Jiaotong University School of Medicine.…”
Section: Methodsmentioning
confidence: 99%
“…A light microscope (Olympus Corp.) was used to capture images to observe sample staining. To analyze the expression of PTPN1, the staining was categorized as previously described (11) and was confirmed by a pathologist at the First Affiliated Hospital of Xi'an Jiaotong University School of Medicine.…”
Section: Methodsmentioning
confidence: 99%
“…Out of the different noncoding genes, we highlight ELF3, TADA3, TP53BP1, UP21, and SIGLEC17P that are upregulated in AMR and connected with the AKT1 and mitogen-activated protein kinase/extracellular signal-regulated kinase pathway. [39][40][41][42][43][44] Moreover, while TP53BP1 has been described to bind to p53 and play a key role in the repair of double-strand DNA breaks, it has also been shown to play a key role in Ig class-switch recombination during antibody genesis, 43,44 a key feature for DSA formation. We have inferred the noncoding genes' functionality based on the idea of co-expression as has been previously done by other authors, [33][34][35] although the fact that coding and noncoding gene are associated does not imply a common biological function.…”
Section: Clinical Researchmentioning
confidence: 99%
“…ALOX5 had been reported to be highly expressed in PTC compared with normal tissues and was related to PTC tumor invasion (Kummer et al, 2012;Reyes et al, 2019). ELF3 was reported to be overexpressed with poor prognosis in PTC patients and likely function as an oncogene in TC (Chen et al, 2019). As for BTN-specific SEadjacent genes identified in this study, SLCO2A1 was reported to be downregulated in follicular thyroid cancer than benign adenoma (Pfeifer et al, 2013), suggesting its role in thyroid tumor pathogenesis.…”
Section: Discussionmentioning
confidence: 53%